A case study on an innovative seismic performance evaluation procedure for irregular RC buildings - Oyguc, Resat A. (Frontiers in Built Environment, 2022)
Assessing the structural capacity of an irregular structure requires an appropriate and robust representation of the analytical model. Conventional procedures are flawed because they lack the reversal effects of higher modes. Therefore, more robust procedures have been tested to accurately capture the capacity of irregular building-type structures. Some of these may be classified as adaptive pushover techniques in which the lateral load vector is revised instantaneously. These adaptive techniques generally refer to SRSS as modal combination rule to superpose the maximum values of the modal quantities. However, this results in an overestimated capacity value. Hence, herein, a force based adaptive multimode pushover method was tested on a plan irregular building using a code developed and implemented into ZEUS-NL. First, an eigenvalue analysis was used to obtain the modal quantities of the considered building, and subsequently the modal story shear forces were obtained using the modal story forces. Following, the lateral load patterns were calculated at each iterative step. Finally, the structure was pushed using this calculated lateral load pattern up to a previously calculated target displacement value using, a three step adaptive pushover analyses. First step is to run an adaptive single-mode pushover analysis considering the first mode. After comparing the fundamental period with a constant threshold limit, it is then decided whether to run an adaptive multimode pushover analysis considering first two modes or to run two adaptive multimode pushover analysis considering the contribution of both the second and third modes. After evaluating the capacity diagram of the considered building, the story drifts were determined. Further, top displacement-time traces were plotted to check which ground motion record reveals the maximum values. Using that ground motion record, interstory drift ratio-time graphs were developed for each story level and compared with the code limit. Base shear-time history traces were then obtained and compared with the tested FAP. Lastly, story shear-interstory drift relations were plotted to investigate the absorbed energy level as an indicator of damage. As a result, for irregular RC structures, the tested procedure is found to be more accurate.